2020
DOI: 10.1080/02770903.2020.1853767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on exercise-induced bronchoconstriction in children and adolescents with asthma

Abstract: The relationship between exercise-induced bronchoconstriction (EIB) and exertional dyspnea in children and adolescents is yet to be fully established.This study examined whether indicators of fractional exhaled nitric oxide (FeNO), forced expiratory volume in 1 s (FEV1) percent predicted at baseline, and dyspnea are useful for predicting children and adolescents with EIB.Methods: We enrolled 184 children and adolescents diagnosed with asthma (mean age 11.2 years); participants were divided into two groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Adults from 18 years should do ≥ 150 min/week of moderate to vigorous activity or ≥ 75 min/week of vigorous activity d p values indicated differences between the 16-and 24-year follow-ups, respectively, and asthma, asthma control and asthma and physical activity regarding median EuroQol visual analogue scale scores obtained using quantile regression. Adjusted for sex, family history of allergic disease and socio-economic status reduced rates of obesity and better HRQoL [40]. However, since information on physical activity and asthma were collected at the same time, no conclusions on the temporal relationships between these variables could be drawn from our data.…”
Section: Discussionmentioning
confidence: 91%
“…Adults from 18 years should do ≥ 150 min/week of moderate to vigorous activity or ≥ 75 min/week of vigorous activity d p values indicated differences between the 16-and 24-year follow-ups, respectively, and asthma, asthma control and asthma and physical activity regarding median EuroQol visual analogue scale scores obtained using quantile regression. Adjusted for sex, family history of allergic disease and socio-economic status reduced rates of obesity and better HRQoL [40]. However, since information on physical activity and asthma were collected at the same time, no conclusions on the temporal relationships between these variables could be drawn from our data.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, when comparing the group of patients suffering from bronchial asthma and EIB with the group of healthy people, it was found that NO concentration is significantly higher for the first group. At the same time, NO level correlation with the increase of bronchial vessel wall permeability and clinical disease severity is noted [21][22][23]. It was found that there is an inverse correlation between the NO concentration and the FEV1 index.…”
Section: Peculiarities Of Effort-induced Bronchospasm Pathogenesis In High-school Teenagersmentioning
confidence: 85%
“…In addition, chlorine exposure when swimming, pollution during running or cycling, cold air exposure, dry air while ice skating exposure or playing hockey, air temperature during hot yoga, have been described as important triggers of EIB (7) . Furthermore, age of children and adolescents also seems to influence EIB prevalence and intensity (8) . Thus, an early diagnosis of EIB, a phenomena that might be asymptomatic especially for mild EIB severity, would help for an earlier and better treatment, which may help to avoid the exclusion of children and adolescents in practice sports.…”
Section: Introductionmentioning
confidence: 99%